Effect of annealing on the microstructure and bonding interface properties of Ag–2Pd alloy wire. Issue 8 (July 2015) - Tseng, Yi-Wei; Hung, Fei-Yi; Lui, Truan-Sheng; Chen, Mei-Yu; Hsueh, Hao-Wen
Highlights: The study developed an Ag–2Pd wire for high electrical conductivity and cost savings. Annealing at 275 °C is suitable for obtaining high-quality Ag–2Pd wire. The IMCs of the Ag–2Pd and Al system were mainly Ag3 (Pd)Al and Ag2 (Pd)Al. Annealing Ag–2Pd wire is a novel and efficient design. Abstract: This study investigated the mechanical and electrical properties of Ag–2Pd wire after thermal annealing. The thermal stability of the tested wire was examined by separately imposing static annealing at 275 °C, 325 °C and 375 °C in a vacuum environment. It was found that annealing the Ag–2Pd wire at 275 °C promoted the formation of a fully annealed structure with equiaxed grains. Annealing Ag–2Pd wire had a shorter heat affect zone (HAZ) length than those of conventional wire, and offered outstanding mechanical properties. A long-term electrical test found Ag3 (Pd)Al and Ag2 (Pd)Al compounds between the Ag–Pd ball and Al pad. These results confirmed the high-reliability properties of annealed Ag–2Pd wires for the wire bonding process.